2019
DOI: 10.1177/0956462419826710
|View full text |Cite
|
Sign up to set email alerts
|

Neurosyphilis is more common in malignant syphilis: A case series and review of the literature

Abstract: Malignant syphilis is a rare skin manifestation of secondary syphilis, which has been reported primarily in the HIV-infected population. This study aimed to investigate the relationship between HIV infection, malignant syphilis, and neurosyphilis through a systematic chart review of 26 malignant syphilis patients seen at our hospital. We also performed a literature review of 83 reported malignant syphilis cases since 1987, when the first case of malignant syphilis co-infected with HIV was reported. We found th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 36 publications
(41 reference statements)
0
14
0
4
Order By: Relevance
“…Malignant syphilis may also lead to more rapid CNS involvement and be first evident together with neurosyphilis with or without HIV 9,48–50 . One group found that neurosyphilis occurred concomitantly in 30% of malignant syphilis patients and only 13.1% of patients with regular secondary syphilis 51 . Possible ocular involvement includes scleral nodules, keratitis, anterior chamber inflammation, and impaired vision 44,52,53 .…”
Section: Clinical Featuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Malignant syphilis may also lead to more rapid CNS involvement and be first evident together with neurosyphilis with or without HIV 9,48–50 . One group found that neurosyphilis occurred concomitantly in 30% of malignant syphilis patients and only 13.1% of patients with regular secondary syphilis 51 . Possible ocular involvement includes scleral nodules, keratitis, anterior chamber inflammation, and impaired vision 44,52,53 .…”
Section: Clinical Featuresmentioning
confidence: 99%
“…9,[48][49][50] One group found that neurosyphilis occurred concomitantly in 30% of malignant syphilis patients and only 13.1% of patients with regular secondary syphilis. 51 Possible ocular involvement includes scleral nodules, keratitis, anterior chamber inflammation, and impaired vision. 44,52,53 Spread to the ears can lead to hearing abnormalities.…”
Section: Systemic Manifestationsmentioning
confidence: 99%
“…A retrospective study reported 26 malignant syphilis patients with typical, serious skin lesions and high non-treponemal tests titers (38). Seven (26.9%) patients were diagnosed with neurosyphilis according to the reactive CSF-VDRL test among these patients.…”
Section: Malignant Syphilismentioning
confidence: 99%
“…One should also be aware of asymptomatic neurosyphilis, which is difficult to diagnose in people living with HIV and often overlooked 9,10 . In addition, a recent study found a much higher proportion (30%) of those with malignant syphilis developed concurrent neurosyphilis as compared to those with the common type of secondary syphilis (13%) 11 . Patients with syphilitic uveitis often have CSF abnormalities facilitating the diagnosis of neurosyphilis.…”
mentioning
confidence: 99%
“…9,10 In addition, a recent study found a much higher proportion (30%) of those with malignant syphilis developed concurrent neurosyphilis as compared to those with the common type of secondary syphilis (13%). 11 Patients with syphilitic uveitis often have CSF abnormalities facilitating the diagnosis of neurosyphilis. Optic syphilis may flare with the JHR with deterioration of visual acuity.…”
mentioning
confidence: 99%